Environmental Engel Curves: Indirect Emissions of Common Air Pollutants - Levinson, Arik; O’Brien, James (The Review of Economics and Statistics, 2019)
Abstract Environmental Engel curves (EECs) describe households’ incomes and the pollution necessary to produce the goods and services they consume. We calculate 29 annual EECs from 1984 to 2012 for point-source air pollutants in the United States, revealing three clear results: EECs slope upward, have income elasticities less than 1, and shift down over time. Even without changes to production techniques, pollution would have declined despite growing incomes. This improvement can be attributed about equally to two trends: household income growth represented by movement along inelastic EECs and economy-wide changes represented by downward shifts in EECs over time.